Clothing habits and chronicity of dermatophytosis: Bridging the gap - Tyagi, Shashank; Kaur, Tejinder; Malhotra, Suresh Kumar (Journal of Pakistan Association of Dermatologists, 2020)
Background Chronic and recurrent dermatophytic infections cause significant distress to the patients. The causal relationship of clothing in these patients remains underscored. The present study highlights the effect of clothing in causing multiple recurrences among Chronic Dermatophytosis patients. Â Methods Patients of chronic recurrent dermatophytosis were enrolled from dermatology OPD and divided into Group I & II, each having patients with less than three & more than three recurrences during the last 6 months respectively. Each group was further divided into three subgroups i.e. Group A, B & C comprising of patients affected with tinea cruris, tinea corporis and both i.e. tinea cruris et corporis respectively. All groups were evaluated in reference to various clothing habits i.e. Type and material of cloth, Frequency of washing clothes, Separate washing of infected clothes, washing, drying and ironing of clothes along with the use of â€œVâ€ shape inner garments. Â Results Comparative evaluation of tinea corporis patients in Group I & II in relation to clothes washed in hot or cold water revealed 73% in Group I & 25% patients in Group II were washing their clothes in hot water while the rest were washing them in cold water. The data was statistically significant. Â Conclusion Clothing habits can be a confounding factor in multiple recurrences of Dermatophytosis and washing clothes in hot water can prevent multiple recurrences of tinea corporis. Â